Communication Patterns Between Students, Teachers and Dormitory Supervisors in Junior High Schools - Dahlia, Fitri; Khaidir, Afriva (LPPM Undiksha, 2025)
A current problem is the tendency towards passive communication patterns among students. Students express difficulty understanding the subject matter but feel embarrassed to ask questions in class. This study aims to analyze communication patterns in junior high schools, focusing on communication patterns between students and teachers, students and dormitory supervisors, and the factors that influence these communication patterns. The study used a qualitative approach and adopted Interpersonal Communication Theory and Symbolic Interaction Theory as theoretical bases. Data collection methods involved interviews, observations, and document analysis using purposive sampling techniques for informant selection. Triangulation of sources and methods was used to ensure the validity of the data. The study results indicate four communication patterns of students with teachers and dormitory supervisors. The first is a passive communication pattern (less talking, minimal eye contact, reluctant to ask questions). The second is an aggressive communication pattern (dominating, sometimes rude, disrupting harmony). The third is a passive aggressive communication pattern (delaying with aggressive motivation, inhibiting cooperation), and the fourth is an assertive communication pattern (self-confident, able to express opinions clearly and openly, dominant among high achieving students). Factors influencing these communication patterns include internal factors (self-concept, interpersonal relationships, past experiences) and family factors (habits of interacting and discussing at home). The implications of this research highlight the importance of promoting assertive communication among students.